Two new species of Pluteus (Agaricales, Pluteaceae) from China - Xu, Jiang; Li, Tai Hui; Justo, Alfredo; Ge, Zai Wei (Phytotaxa, 2015)
Two new species of Pluteus section Pluteus, P. griseodiscus and P. purpureofuscus, are described from China. Pluteus griseodiscus is characterized by the pale basidiomata, non-pigmented lamellar edges, thick-walled cheilocystidia and the presence of caulocystidia. Pluteus purpureofuscus is characterized by a purple-brown pileus, presence of clamp-connections, and growth on coniferous wood. The phylogenetic position of both species is also discussed based on nrITS data.